TURF IN ELECTRICITY GENERATION 1945-2000 - Coleman, Cathal (Management and Administration Journal, 2025)
This paper examines the industrial harvesting of turf and its use in electricity generation in Ireland from 1945 to 2000. It explores the commercial exploitation of Irish bogs which had been neglected for centuries. Exploitation achieved impetus when some revolutionaries such as Todd Andrews advocated economic self-sufficiency. With Government approval, Bord na Móna was created in 1945. Another state body, the Electricity Supply Board (ESB), established turf-fired power plant. These developments had a significant economic impact until the mid 1980s. Thereafter, a combination of ageing plant, and supra-national environmental regulation led to the closure of power stations and the cessation of peat harvesting.